Implementing the flipped classroom methodology to the subject "Applied computing" of the chemical engineering degree at the University of Barcelona - Montserrat Iborra; Eliana Ramírez; Jordi Hug Badía; Roger Bringué; Javier Tejero (OmniaScience, 2017)
This work is focus on implementation, development, documentation, analysis and assessment of flipped classroom methodology, by means of just in time teaching strategy, in a pilot group (1 of 6) of the subject "Applied Computing" of Chemical Engineering Undergraduate Degree of the University of Barcelona. The results show that this technique promotes self-learning, autonomy, time management as well as an increase in the effectiveness of classroom hours.